Enzyme linked immunosorbent assay (ELSA) investigation for Human Kisspeptin and progesterone Levels in female having regular menstrual cycle - Abbas, Ahsan K. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Kisspeptin the product of the gene Kiss1 is a G-protein coupled receptor legend for GPR54. Kiss1 was originally identified as a human metastasis suppressor gene that has the ability to suppress melanoma and breast cancer metastasis. It is recently become clear that kisspeptin-GPR54 signaling has an important role in initiating GnRH secretion at puberty, the extent of which is an area of ongoing research. Objective: The present study was designed to determine the change of plasma kisspeptin levels during the menstrual cycle Materials & Methods: A total of 20 women from friends and relatives pool were involved in this study. Selected from frinds and relative .They were selected after measuring their progesterone level on day 21 of menstrual cycle (excluding women who have anovulate menstrual cycle; low level of progesterone) , and then on 1 -5 day of the next menstrual cycle. All measurements were done in Teaching laboratories in Baghdad Teaching Hospital in Baghdad/Iraq. Five mls of blood withdrawn from each selected women by veinpuncture of selected women. ELISA technique was used for the measurement of serum kisspeptin - 1and progesterone level. Data were expressed as a mean ±SD. Results were evaluated using the student ttest for paired data. Conventional methods were used for the correlation and regression analyses. Results: Results obtained showed that the levels of serum kisspeptin and progesterone were significantly higher on day 21of menstrual cycle than during menstruation period with p<0.01, also it was found a significant positive correlation of kisspeptin level with progesterone level (r= 0.77 ,p<0.01). Conclusion: The results determine the role of kisspeptin on ovulation, and give a possibility for its beneficial manipulation of human fertility.